Histopathological and Transcriptional Changes in Silkworm Larval Gonads in Response to Chlorfenapyr Exposure - Tao Li; Changxiong Hu; Zenghu Liu; Qiongyan Li; Yonghui Fan; Pengfei Liao; Min Liu; Weike Yang; Xingxing Li; Zhanpeng Dong (Insects)
Chlorfenapyr is a widely used insecticide known to harm non-target insects, but its effects on reproductive development in the silkworm (Bombyx mori L.) remain incompletely understood. In this study, we investigated the histopathological and transcriptional changes in the gonads (ovaries and testes) of newly molted fifth-instar silkworm larvae exposed to chlorfenapyr. Histopathological analysis revealed delayed gonadal development, a reduction in oogonia and oocytes in the ovaries, and decreased numbers of spermatocytes in the testes. Transcriptome analysis identified significant differentially expressed genes (DEGs), mainly enriched in pathways such as “Drug metabolism—cytochrome P450”, “Insect hormone biosynthesis”, and “Ribosome”. Key up-regulated genes included members of the cytochrome P450 family (CYP6B5, CYP9f2, CYP6B6), glutathione S-transferases (GSTT1, GST1), and juvenile hormone-related enzymes (JHAMT, JHEH), indicating active detoxification and hormonal regulation responses. Several transcription factor families, particularly C2H2, HB-other, and TRAF, exhibited altered expression, suggesting roles in stress adaptation. Protein–protein interaction (PPI) network analysis identified hub genes such as EcR, Kr-h1, and various ribosomal proteins, highlighting their potential involvement in reproductive development. Quantitative PCR (qPCR) validated the transcriptomic data, confirming the reliability of the results. Overall, these findings enhance our understanding of chlorfenapyr’s impact on silkworm reproductive development and the underlying molecular mechanisms, providing valuable insights for sustainable pest management and ecological risk assessment of insecticides.